2023
DOI: 10.3389/fneur.2023.1099758
|View full text |Cite
|
Sign up to set email alerts
|

New onset or relapsing neuromyelitis optica temporally associated with SARS-CoV-2 infection and COVID-19 vaccination: a systematic review

Abstract: BackgroundNeuromyelitis optica spectrum disorder (NMOSD) is a rare chronic neuroinflammatory autoimmune condition. Since the onset of the COVID-19 pandemic, there have been reports of NMOSD clinical manifestations following both SARS-CoV-2 infections and COVID-19 vaccinations.ObjectiveThis study aims to systematically review the published literature of NMOSD clinical manifestations associated with SARS-CoV-2 infections and COVID-19 vaccinations.MethodsA Boolean search of the medical literature was conducted be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…NMOSD is an autoimmune disease that causes demyelination of the central nervous system including the optic nerve and the spinal cord. It was suggested that COVID-19 vaccinations are associated with the development of NMOSD in a systematic review of studies in which 26 patients experienced new demyelinating symptoms related to NMOSD [39]. In those patients, 54% (14/26) of the patients received an mRNA vaccine, 31% (8/26) of the patients received a viral vector vaccine, and 15% (4/26) of the patients received an inactivated COVID-19 vaccine [39].…”
Section: Serious Complications After Sars-cov-2 Vaccinationmentioning
confidence: 99%
“…NMOSD is an autoimmune disease that causes demyelination of the central nervous system including the optic nerve and the spinal cord. It was suggested that COVID-19 vaccinations are associated with the development of NMOSD in a systematic review of studies in which 26 patients experienced new demyelinating symptoms related to NMOSD [39]. In those patients, 54% (14/26) of the patients received an mRNA vaccine, 31% (8/26) of the patients received a viral vector vaccine, and 15% (4/26) of the patients received an inactivated COVID-19 vaccine [39].…”
Section: Serious Complications After Sars-cov-2 Vaccinationmentioning
confidence: 99%
“…Considering evidence supporting a temporal increase in the prevalence of NMOSD, 8 similar to other demyelinating diseases (i.e. MS and Parkinson’s disease), 9 and that SARS-CoV-2 infection may precede NMOSD onset, 10 it is important to describe the recent burden of NMOSD in the United States in the post-pandemic era, including its prevalence by age, sex, and race.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, neurological dysfunction associated with autoimmunity was also reported. Cases included ADEM (Nabizadeh et al, 2023), Guillain-Barré syndrome (GBS; Pimentel et al, 2023), MS and NMOSD onset (Harel et al, 2023), encephalitis (Nabizadeh et al, 2022), among others. As COVID-19 became widespread worldwide, those manifestations turned into a public health concern.…”
Section: Introductionmentioning
confidence: 99%
“…development after COVID-19 in unvaccinated patients(Avila et al, 2023;Pignolo et al, 2021;Palao et al, 2020). A systematic review found 18 cases of MOGAD following infection(Mirmosayyeb et al, 2023), while another one revealed 15 cases of NMOSD(Harel et al, 2023). Another review, which encompassed any case of CNS in ammatory demyelinating disease (IDD), found higher numbers for new onset MOGAD, with 27 cases(Lotan et al, 2022).…”
mentioning
confidence: 99%